The first transcriptome sequencing and analysis of the endangered plant species Picea neoveitchii Mast. and potential EST-SSR markers development. Issue 1 (1st January 2019) - Chang, Pan; Zhu, Ling; Zhao, Mengran; Li, Chao; Zhang, Yi; Li, Lingli
Abstract: Picea neoveitchii Mast. is a rare and endangered evergreen coniferous tree species in China. P. neoveitchii grows within a specific ecological and geographical range. Here, we performed transcriptome sequencing of P. neoveitchii using the Illumina high-throughput deep sequencing technology with the following aims: (i) to perform de novo transcriptome assembly, (ii) to perform transcriptome assembly with functional annotation, (iii) to study the candidate genes involved in the biosynthesis of cellulose and lignin, (iv) to identify and analyse the transcription factors, and (v) to develop potential expressed sequence tag–simple sequence repeat (EST-SSR) markers for future population genomic and genome-wide association studies in P. neoveitchii . This is, to the best of our knowledge, the first study to provide a comprehensive transcriptome of P. neoveitchii . The transcriptome data contained 12.97 gigabase pairs (Gbp) for a total of 120, 951 different transcripts belonging to 66, 022 unigenes. In addition, we classified enzymes involved in the biosynthesis of cellulose and lignin and identified and analysed the transcription factors involved in stress responses, growth and development. Based on the larger than 1 kb unigenes, 1, 814 EST-SSR markers were shown. Our results demonstrated that the transcriptome analysis is a valuable technology for non-model species with large genomes and this dataset will be an essential resource for future genetic and genomic research in P. neoveitchii .